Show Me My DNA: Engaging Florida Elementary Students in Biotechnology - Patricia Fajardo-Cavazos; Wayne L. Nicholson (EDIS, 2006)
MB-003, a 3-page fact sheet by Patricia Fajardo-Cavazos and Wayne L. Nicholson, gives step-by-step instructions for an elementary school class exercise in which students isolate visible strands of their own DNA using easily obtained materials. The value of this exercise is explained. Published by the UF Department of Microbiology, October 2006.